1995
DOI: 10.1007/bf00120302
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate cement: in vitro and in vivo studies of the α-tricalcium phosphate-dicalcium phosphate dibasic-tetracalcium phosphate monoxide system

Abstract: In this paper, calcium phosphate cement consisting of ~-tricalcium phosphate (a-TCP), dicalcium phosphate dibasic (DCPD) and tetracalcium phosphate monoxide (TeCP) was investigated in vitro and in vivo. Measurements of compressive strength against soaking time in simulated body fluid (SBF) showed a rapid increase of the hardness for the first 7 days. The gained strength was retained up to 1 year and the maximal mean value was 94.7 (_+ 14.4)MPa. X-ray diffraction (XRD) and scanning electron microscopy (SEM) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 17 publications
3
32
0
2
Order By: Relevance
“…Dieser Vorteil ist gerade beim Einsatz am jüngeren Patienten von enormer Bedeutung. Die bisher untersuchten Kalziumphosphatzemente wurden den biomechanischen Anforderungen jedoch nicht gerecht und schnitten immer schlechter als PMMA ab [1,8,9].…”
Section: Diskussionunclassified
“…Dieser Vorteil ist gerade beim Einsatz am jüngeren Patienten von enormer Bedeutung. Die bisher untersuchten Kalziumphosphatzemente wurden den biomechanischen Anforderungen jedoch nicht gerecht und schnitten immer schlechter als PMMA ab [1,8,9].…”
Section: Diskussionunclassified
“…Hydroxyapatite (HA) granules [1][2][3] andtricalcium phosphate paste (P ) [4][5][6] are widely used as bone substitutes in patients with fractures, bone defects or absorption of the alveolar ridge 7,8) . On the other hand, animal studies have led to the developments of new techniques, including autogenous bone onlay grafting [9][10][11][12] and artificial bone block 3,6,[13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Paste-like calcium phosphate cements thus developed may be classified into two groups on the basis of the type of hardening reaction: i) acidbase reaction among calcium phosphates to form apatite or calcium hydrogenphosphate dihydrate [CaHPO 4 3) A representative example of the latter type is hardening caused by hydrolysis of ¡-tricalcium phosphate [Ca 3 (PO 4 ) 2 ] (¡-TCP). 4), 5) Recently, amorphous ¢-TCP ground with a ball mill has been found to be subject to hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…4), 5) Recently, amorphous ¢-TCP ground with a ball mill has been found to be subject to hydrolysis. 6) We reported that H 2 Oincorporated ¢-TCP ground with a mortar grinder is easily hydrolyzed 7), 8) and hardened when mixed with a 2.5 wt % disodium hydrogenphosphate [Na 2 HPO 4 ] aqueous solution.…”
Section: Introductionmentioning
confidence: 99%